Program DASHAT: Strategi Pemerintah Simeulue sebagai Upaya Penanganan Stunting - Afriandi, Fadli; Rahmadani, Saumi (Bahasa Indonesia, 2025)
Stunting is a health issue in children, particularly toddlers, characterized by impaired physical and brain development due to prolonged nutritional deficiencies. Due to sectoral egos among government agencies and inadequate socialization efforts, addressing stunting remains a significant challenge. Simeulue Regency faces numerous obstacles and is among the regions with the highest stunting rates in the area. The aim of this study is to identify the strategies employed by the Simeulue Government to reduce stunting. This research uses a qualitative approach, collecting data through documentation and observation techniques. The findings reveal that the Simeulue Government has implemented the Dapur Sehat Atasi Stunting (DASHAT) program. This program includes sub-programs such as Ayah Susi, Ma Andong, and Maninting, which are philosophically rooted in the local language of the region. These strategies have successfully reduced stunting rates in Simeulue Regency. This success is evidenced by the fact that Simeulue Regency was awarded the best recognition in Aceh for addressing stunting in 2024